Strategic planning in financial institutions - Kenneth C. Krogh (South African Journal of Business Management, 1982)
The article outlines an approach to strategic planning for financial institutions in which functional strategic plans are first developed for each business unit or unique area of service in the organization. The bank's overall strategic plan is then developed by approving or modifying individual plans so that resources are channelled into areas offering the greatest potential for achievement of the bank's goals. The strategic planning cycle for each line of business should include eight planning elements: mission statement; internal analysis including the unit's strengths and weaknesses; external analysis which includes opportunities and threats in the environment; goals and objectives; strategies for action; management review action; planning for implementation; and continuous evaluation of performance of both people and products in terms of the strategic plan and stated objectives. Several models are shown to illustrate the process.
Keywords: 650